Pengaruh Kinerja Keuangan Terhadap Nilai Perusahaan Dengan Good Corporate Governance Sebagai Variabel Moderasi Pada Bank Yang Terdaftar Di BEI Tahun 2019-2021 - Nina Lelawati; Ardiansyah Japlani; Fredyana Natria Anggraini (Jurnal Manajemen DIVERSIFIKASI, 2024)
Based on the tests that have been carried out by researchers using the classical assumption test (multicollinearity test, autocorrelation test, heteroscedasticity test), hypothesis testing (panel data regression model using the fixed effect model), t test and R2 test it is found that financial performance affects the value company and good corporate governance moderate the relationship between financial performance and company value at banks listed on the IDX for 2019-2021.